2018
DOI: 10.1101/443671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic whale counting in satellite images with deep learning

Abstract: Despite their interest and threat status, the number of whales in world's oceans remains highly uncertain. Whales detection is normally carried out from costly sighting surveys, acoustic surveys or through high-resolution orthoimages. Since deep convolutional neural networks (CNNs) achieve great performance in object-recognition in images, here we propose a robust and generalizable CNN-based system for automatically detecting and counting whales from space based on open data and tools. A test of the system on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…As deep learning is used to detect, identify and classify individuals in automatic monitoring data, such tools can be scaled up to help monitor populations. For instance population size can be estimated by counting individuals (Guirado, Tabik, Rivas, Alcaraz‐Segura, & Herrera, ; Norouzzadeh et al, ). By extension, information such as population distribution or density can also be calculated from this data as it has already been done with traditional methods (Rovero et al, ).…”
Section: Overview Of Applications In Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…As deep learning is used to detect, identify and classify individuals in automatic monitoring data, such tools can be scaled up to help monitor populations. For instance population size can be estimated by counting individuals (Guirado, Tabik, Rivas, Alcaraz‐Segura, & Herrera, ; Norouzzadeh et al, ). By extension, information such as population distribution or density can also be calculated from this data as it has already been done with traditional methods (Rovero et al, ).…”
Section: Overview Of Applications In Ecologymentioning
confidence: 99%
“…Therefore, training datasets often contain thousands to millions of examples, depending on the task, the number of items to detect and the desired performance (Marcus, ). Good results have been obtained with smaller training datasets with only several hundred examples per class (Abrams et al, ; Fairbrass et al, ; Guirado et al, ) opening the approach for most fields of ecology. Yet, overall, the bigger the training dataset, the better the classification accuracy will be (Marcus, ).…”
Section: Implementing Deep Learning: Challenges and Guidelinesmentioning
confidence: 99%
“…In addition, several studies are being conducted to investigate the use of deep-learning applications for wildlife monitoring with the aid of aerial photographs. Maire et al [51] showed the feasibility of using the simple linear iterative clustering (SLIC) and CNN methods for the detection of wild marine mammals, and Guirado et al [52] detected whales using satellite images in combination with a CNN-based method to detect the presence of whales and for whale counting.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the most timeconsuming aspects of biological observation has been identifying species, historically requiring taxonomic experts. Deep learning techniques enable automated classification of species from a variety of platforms, including: opportunistic citizen science visual observations (e.g., redmap.org.au; iNaturalist.org; Pimm et al, 2015); benthic photo quadrats (BisQue; Rahimi et al, 2014, Fedorov et al, 2017; cabled video observatories (Marini et al, 2018); unmanned underwater vehicles (Qin et al, 2015;Sung et al, 2017); acoustic-sensing hydrophones (Dugan et al, 2015;McQuay et al, 2017); plankton-sensing flow cytometers (Göröcs et al, 2018); and satellite imagery (Guirado et al, 2018). Taxonomic experts are still very much needed for developing datasets as inputs to this modeling approach.…”
Section: Artificial Intelligencementioning
confidence: 99%